Credit risk spillovers and cash holdings - Lei, Jin; Qiu, Jiaping; Wan, Chi; Yu, Fan; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2018)
This paper examines how credit risk spillovers affect corporate Financial Flexibility and bank loan contracting. We construct separate empirical proxies to disentangle the two channels of credit risk spillovers — credit risk contagion (CRC), which increases industry peers’ distress likelihood; and product market rivalry (PMR), which strengthens rivals’ competitive position. We show that firms facing greater CRC hold more cash, make lower payouts, and must contend with less favorable bank loan terms. In contrast, PMR generally has opposite, albeit weaker, effects. Our findings suggest that credit risk spillovers, especially CRC, play an important role in corporate liquidity management. Valuation Insight: Credit risk contagion susceptibility appears to negatively affect a firm’s valuation. This comes about through the firm electing to hold more cash and accepting less favorable bank loan terms.
51 p. ; Includes bibliographical references (pp. 28-35). ; "July 30, 2018"; The authors "are grateful to George Batta, Eric Helland, Eric Hughson, Oana Tocoian, Angela Vossmeyer, and participants at the CMC Summer Research Workshop for helpful comments."
Keywords: Credit risk contagion; Product market rivalry; Financial distress; Cash holdings; Payout ratio; Bank loan contracting